The performance analysis of private conventional banks: a case study of Bangladesh - Haque, Samina (© 2013 IOSR Journal of Business and Management (IOSR-JBM), 2016)
This article was published in IOSR Journal of Business and Management (IOSR-JBM) [© 2013 IOSR Journal of Business and Management (IOSR-JBM)] and the definite version is available at : https://www.academia.edu/4858303/The_Performance_Analysis_of_Private_Conventional_Banks_A_Case_Study_of_Bangladesh The article website is at: http://www.iosrjournals.org/iosr-jbm.html